Modelagem de sistemas de geração distribuída com motores de combustão interna invertidos a biogás - Campos, Bruna Andrade Parcianello (2018)
The distributed generation, as a mean of energy generation, has earning more and more space in brazilian electric sector. A relevant alternative, mainly because of the environment benefits, is biogas, obtained from biomass and used as a fuel in internal combustion engines (ICEs). In this scenario, the P&D “Entre Rios do Oeste” (ERO) project, executed by CIBiogás and FPTI and financed by Copel is fitted, which predicts efficient use of the biogas produced by a group of farmers in the west region of Paraná state, through a motor-generator set responsible for transforming the biogas produced by the farmers into electricity. Considering that still there is little results when it comes to computational modeling for ICEs converted to biogas and the opportunity that the ERO project presents, it was considered relevant the development of a computational model of a distributed generation system based in a biogas moved ICE. Following this idea, the present paper intends to develop this modeling from the representation of a biogas conversion based in a gasoline ICE Mean Value Model (MVM). The adjustments incorporated to the model to represent a biogas converted ICE, were basically: an operating speed scheduling, the representation of the biogas conversion by the changing in its main parameters, and a power scheduling for reaching the power of the case of interest. It was then, used to incorporate a distributed generation system, which was modeled through Matlab/Simulink software. Thus, it was verified the functionality and the behavior of the complete model throughout dinamics and statics points of view through computational simulations with variations in its speed and voltage regulator’s reference, as well as faults simulations. The results showed that the model’s dynamic is coherent with a synchronous generation system. The complexity of the excitation system model and the dynamic of the ICE on its own, had insignificant influence on the global dynamics of the system. In other hand, the tests pointed out the non linear behavior of the ICE, which had a huge impact in the system’s dynamics, becoming clear the necessity of representing properly the linearization of the non linearity of the throttle body in the speed controller. Still, the motor-generator inertia standed out in the system’s global dynamics either, which represents the flywheel of the real system. Finally, the obtained result was a model capable of becoming a mean of subsequent technical studies in the scope of distributed generation. The model was developed for phasorial simulations aiming applications in studies of connection to the distribution grid.